Lidar-based research in the Phokian Kephissos Valley - Sporn, Katja; Kennedy, Will M. (Journal of Greek Archaeology, 2025)
In 2018, an interdisciplinary German-Greek collaborative project was launched in the central Kephissos Valley in ancient Phokis, under the direction of Petros Kounouklas from the Ephorate of Phthiotida and Evrytania and Katja Sporn, Director of the German Archaeological Institute at Athens (DAI Athens). The aim of the Kephissos Valley Project (KEP) is to reconstruct the settlement development and respective sanctuaries, necropoleis, and infrastructure throughout Antiquity within its natural environmental context. In addition to researching the impact of specific historical events (e.g., destructions, re-settlements, etc.), particularly the question of how natural and/or human-induced phenomena (i.e., possible changes in the river course and water ways, ramifications of floods and earthquakes, etc.) affected the use of the fertile fields on both sides of the Kephissos river and the re-location of settlements, is of great importance. The chronological range of the project spans from the Bronze Age to Late Antiquity but mainly focuses on the periods from the foundation of the Greek city-states to Late Antiquity.